New additive type amorphous-carbon/Zn modifier of the thermal conductivity of alcohol fuel - Potensa, Bruno Santos [UNESP]; Martins, Grazieli Olinda [UNESP]; Lanfredi, Silvania [UNESP]; Lima Nobre, Marcos Augusto [UNESP] (Trans Tech Publications, 2015)
A functional inorganic-additive modifier of the thermal conductivity of biofuel type alcohol anhydrous was developed based on an amorphous carbon nanocomposite containing dispersed zinc. Dispersion and modification of thermal conductivity in biofuels type anydrous alcohol were considered, as well as in petro-diesel and a blend of biodiesel and petro-diesel. Fuels, alcohol, diesel and biodiesel acted as a continuous medium dispersing the particles of C/Zn. Both thermal conductivity and thermal resistivity measurements were carried out showing that the amorphous nanocomposite particles C/Zn act as an additive to improve the thermal conductivity of alcohol. The same phenomenon has not been identified for diesel, biodiesel and its blends. Increasing the thermal conductivity of the alcohol generated by adding of particles is discussed as a function of the concentration and molecular interactions on the surface of additive particles.
Keywords: Additive; Biofuel; Carbon/Zn; Nanocomposite; Thermal conductivity